A study on Islamic Banking institutions on Malaysia: Focus on the growth, performance and financing product - Siti Nurulhuda Ibrahim (2007)
This study was to determine the growth of Islamic Banking institution in Malaysia from earlier establishment, the performance of it and its product offered to customer which was in this study the researcher has more focused about financing (BaiBithaman Ajil financing). The study has looked at the experience of Islamic banking institution in Malaysia from 1983 to 2006 which was showed the growth of total asset, deposit and financing of this institution. Then to measure its performance, the researcher has looked for the changes in the profitability ratio over time from 2001 until 2005 that means cover five-year period of experience whether going parallel with conventional banks. This will answer to the target place by BNM as the long-term objective of BNM is to create an Islamic banking system operating on a parallel basis with the conventional banking system and examined the performance enable us to draw a conclusions about Islamic banking institution's financial health and its variation over time. Then issue about Islamic financing also been discussed to make people more understand about its mode of financing, which was in this study, the researcher has evaluated about BBA (Bai-Bithaman Ajil financing).